M1 macrophages act as LTβR-independent lymphoid tissue inducer cells during atherosclerosis-related lymphoid neogenesis. (22nd November 2013) - Guedj, Kevin; Khallou-Laschet, Jamila; Clement, Marc; Morvan, Marion; Gaston, Anh-Thu; Fornasa, Giulia; Dai, Jianping; Gervais-Taurel, Marianne; Eberl, Gerard; Michel, Jean-Baptiste; Caligiuri, Giuseppina; Nicoletti, Antonino
Abstract: Aims: The goal of this study was to characterize the role of inflammatory macrophages in the induction of the vascular smooth muscle cell (VSMC)-mediated formation of aortic tertiary lymphoid organs (TLOs). Methods and results: Mouse bone marrow-derived M1 macrophages acted as lymphoid tissue inducer cells. Indeed, they expressed high levels of tumour necrosis factor (TNF)-α and membrane-bound lymphotoxin (LT)-α, two inducing cytokines that triggered expression of the chemokines CCL19, CCL20, and CXCL16, as did M1 supernatant. The blockade of LTβR signalling with LTβR-Ig had no effect, whereas that of TNFR1/2 signalling reduced chemokine expression by VSMCs in both wild-type (WT) and LTβR KO mice, demonstrating that LTβR signalling is dispensable for the M1-inducing effect. This effect was corroborated by the development of TLOs observed in LTβR KO->apolipoprotein E knockout (ApoE KO) aortic segments after orthotopic transplantation. Furthermore, treatment of ApoE KO mice with anti-TNF-α antibody decreased the number and incidence of aortic TLOs. Finally, lymphoid nodules composed of T and B cells formed in in vivo -implanted scaffolds seeded with VSMCs previously stimulated ex vivo by M1-conditioned medium. Conclusions: These results are the first to identify M1 macrophages as inducer cells that trigger the expression of chemokines by VSMCs independently of LTβR signalling. We propose that the dialogue between macrophages and VSMCs—established across the vascular wall—contributes to the formation of aortic TLOs.